Personality & negotiation: a study with a new approach - Saraiva, Manuel Andrade (2015)
After a hiatus in the research of individual di erences within negotiation, there's been a surge of renewed interest for the past years followed by several new ndings. With an increasing trend of interdependence and strategic alliances governing the current corporate reality, negotiation is rapidly becoming a paramount element in managers daily working lives, and now more than ever there is a need to understand how these particular moments of interpersonal dynamics can be leveraged towards better outcomes for both sides, whether in terms of economic gain or relationship development. The present study is aimed at exploring the e ects that personality, as structured by the Five-Factor Model, has over negotiation behavior and decision-making in order to not only compare any possible ndings to previous theoretical constructs as well as past research, but also to prescribe advice to future negotiators. For this purpose, data from a sample of volunteering participants was collected in regard to their personality and behavior during two computerized negotiation simulations, one with the potential for joint gains and the other following a more traditional bargaining scenario. Signi cant results for both settings were found, with the personality dimensions of Agreeableness, Conscientiousness and Extraversion frequently reoccurring as the most statistically relevant, although exhibiting di erent roles according to the type of negotiation and measure being registered. Findings thus suggest a multidimensional relationship between personality and situational variables given how speci c traits can either become liabilities or assets depending on whether the potential for value creation is present or not.